Ser diferente é normal - Bernhard, Cristiane Otília Colossi; Santos , Eliana Ferreira dos; Carvalho , Elza Dias de Oliveira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver p´df